119k views
3 votes
If m * n = √(m²-n²) then 5 * 3 = ​

2 Answers

6 votes


m \cdot n = √(m^2 -n^2)\\\\\text{When m =5 and n =3,}\\\\\\5\cdot 3 = √(5^2 -3^2) =√(25 -9) = √(16) = 4

User DrC
by
5.8k points
3 votes


\huge\text{Hey there!}


\huge\textbf{Assuming:}


\mathbf{m* n = √((m^2 - n^2))}


\huge\textbf{Solving:}


\mathbf{\rightarrow 5* 3 = √((5^2 - 3^2))}


\mathbf{\rightarrow 15 = √((5*5 - 3*3))}


\mathbf{\rightarrow 15 = √((25 - 9))}


\mathbf{\rightarrow 15 = √(16)}


\mathbf{15\\eq4}


\huge\textbf{Thus, this answer should be:}


\huge\boxed{\boxed{\textsf{This statement is most likely: \boxed{\textsf{FALSE}}}}}\huge\checkmark


\huge\text{Good luck on your assignment \& enjoy your day!}


\frak{Amphitrite1040:)}

User Mohad Hadi
by
5.7k points